2017
DOI: 10.1080/09540105.2017.1313821
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive double antibody sandwich ELISA for the quantification of phosvitin

Abstract: An effective double antibody sandwich ELISA (DAS-ELISA) method based on monoclonal (mAb) and chicken egg yolk IgY antibodies was developed to determine phosvitin (PV) content in therapeutic and functional products. Leghorn laying hens were immunized with purified PV to produce anti-PV IgY antibody in the egg yolk. High anti-PV IgY titer obtained from the egg yolks collected during 4-10 weeks of the immunization period contained approximately 6.2% of specific anti-PV IgY in total IgY. The PV detection range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Although there are some studies of macromolecules detection in food samples through IgY-based immunoassays, the number of IgY against various macromolecules is still limited. These examples also give a clear clue that the advantage of IgY combined with IgG for sandwich immunoassays to reduce background derived from nonspecific binding or heterophil antibodies should be expanded in further studies.…”
Section: Chicken Igy-based Immunoassays For Detecting Macromoleculesmentioning
confidence: 99%
“…Although there are some studies of macromolecules detection in food samples through IgY-based immunoassays, the number of IgY against various macromolecules is still limited. These examples also give a clear clue that the advantage of IgY combined with IgG for sandwich immunoassays to reduce background derived from nonspecific binding or heterophil antibodies should be expanded in further studies.…”
Section: Chicken Igy-based Immunoassays For Detecting Macromoleculesmentioning
confidence: 99%
“…Immunoassays can be classified as either competitive, in which the measured signal is associated with a limited amount of antibodies that failed to capture the analyte; or noncompetitive, in which the measurement of the signal is associated with antibody that binds the analyte (Li, Wu, Song, Zheng, & Kuang, 2019;Suryoprabowo et al, 2019). Theoretical study has showed that noncompetitive immunoassays are good sensitivity, precision, a wider working range, and comparability with competitive immunoassays (Gujral, Yoo, Bamdad, Suh, & Sunwoo, 2017). Thus, researchers have sought to develop noncompetitive immunoassays for the determination of small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoassay based on antigen-antibody interaction has many excellent features, such as being accurate, quick, sensitive and high throughput (Gomaa & Boye, 2015;Kong et al, 2017;Shen et al, 2017;Tighe, Ryder, Todd, & Fairclough, 2015). It has been successfully applied in detecting low molecular mass organic contaminations in food, especially in screening large numbers of samples, playing an important role in food safety regulation (Anfossi, Di Nardo, Giovannoli, Passini, & Baggiani, 2015;Bolarinwa, Orfila, & Morgan, 2014;Gujral, Yoo, Bamdad, Suh, & Sunwoo, 2017;. However, due to the lack of epitope of haptens, the production of antibodies with high affinity and high specificity is still one of the bottlenecks of immunoassay for some small molecules (Luo et al, 2014;Luo et al, 2014;Mu et al, 2015;Romestand et al, 2010;Romestand et al, 2010;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%